Alterations of ceramide synthesis induce PD-L1 internalization and signaling to regulate tumor metastasis and immunotherapy response - Wofford, Wyatt; Kim, Jisun; Kim, Dosung; Janneh, Alhaji H.; Lee, Han Gyul; Atılgan, Cansu; Oleinik, Natalia; Kassir, Mohamed Faisal; Saatçi, Özge; Chakraborty, Paramita; Tokat, Ünal Metin; Gencer, Salih; et al. (My University, 2024)
Programmed death ligand 1, PD-L1 (CD274), facilitates immune evasion and exerts pro-survival functions in cancer cells. Here, we report a mechanism whereby internalization of PD-L1 in response to alterations of bioactive lipid/ceramide metabolism by ceramide synthase 4 (CerS4) induces sonic hedgehog (Shh) and transforming growth factor ? receptor signaling to enhance tumor metastasis in triple-negative breast cancers (TNBCs), exhibiting immunotherapy resistance. Mechanistically, data showed that internalized PD-L1 interacts with an RNA-binding protein, caprin-1, to stabilize Shh/TGFBR1/Wnt mRNAs to induce ?-catenin signaling and TNBC growth/metastasis, consistent with increased infiltration of FoxP3+ regulatory T cells and resistance to immunotherapy. While mammary tumors developed in MMTV-PyMT/CerS4?/? were highly metastatic, targeting the Shh/PD-L1 axis using sonidegib and anti-PD-L1 antibody vastly decreased tumor growth and metastasis, consistent with the inhibition of PD-L1 internalization and Shh/Wnt signaling, restoring anti-tumor immune response. These data, validated in clinical samples and databases, provide a mechanism-based therapeutic strategy to improve immunotherapy responses in metastatic TNBCs.
Keywords: Ceramide; Cers4; CP: Cancer; CP: Metabolism; Immunotherapy; Metastasis; PD-L1; Sonic Hedgehog; Sphingolipid